Enzyme Inhibitors and Activators 2017
DOI: 10.5772/67248
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Inhibitors and Activators

Abstract: Enzymes are very effective biological catalysts that accelerate almost all metabolic reactions in living organisms. Enzyme inhibitors and activators that modulate the velocity of enzymatic reactions play an important role in the regulation of metabolism. Enzyme inhibitors are also useful tool for study of enzymatic reaction as well as for design of new medicine drugs. In this chapter, we focused on the properties of enzyme inhibitors and activators. Here we present canonical inhibitor classification based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 35 publications
(45 reference statements)
0
20
0
Order By: Relevance
“…Our previous work with Gd-based nanozymes showed that L-cysteine amino acid acts as a reversible inhibitor [ 51 , 52 ]. In that case, L-cysteine did not act as a catalyst poison but instead, it interacted with the nanozyme through a competitive inhibition process where there was a competition between L-cysteine and the peroxidase substrates to bind to the surface of the nanozyme.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work with Gd-based nanozymes showed that L-cysteine amino acid acts as a reversible inhibitor [ 51 , 52 ]. In that case, L-cysteine did not act as a catalyst poison but instead, it interacted with the nanozyme through a competitive inhibition process where there was a competition between L-cysteine and the peroxidase substrates to bind to the surface of the nanozyme.…”
Section: Resultsmentioning
confidence: 99%
“…For the hydrolysis reaction, two further inhibition mechanisms are conceivable. On the one hand, parts of two substrate molecules could bind to the active center of the enzyme and thus form a dead-end ES 2 complex ( Lopina, 2017 ). The conformational flexibility of the 3′- and 5′-phosphate moieties observed for the alarmone species, which allows interaction with a broad spectrum of intracellular targets ( Steinchen and Bange, 2016 ), could facilitate this process.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a metal dependency of this enzyme cannot be deduced safely at this point. The effects of EDTA could also result from an overall sensibility of the enzyme structure for changes in its environment (Bisswanger 2014;Robinson 2015;Lopina 2017). The negative effect of the anionic detergent SDS on the activities of all three novel agarases from M. elongatus PORT2 indicated their localization in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%